Teleparalelismo equivalente simétrico à Relatividade Geral no limite de campo fraco - Simijaca Salcedo, Fabian Leonardo (2023)
The study of the formalism of symmetric teleparalelism equivalent to general relativity has recently been studied by the community to solve the phenomenological problems that general relativity presents, as inflation and dark energy. In particular, this work studies the degrees of freedom of symmetric teleparalelism equivalent on the weak field approach. For this, a revision of General Relativity is first made in order to learn how to identify the degrees of freedom of theory and thus to guide the study of symmetric teleparalelism equivalent.